High season : a novel - Bishop, Katie, 1992- (St. Martin's Press, 2025)
"On a beautiful summer's night twenty years ago, troubled seventeen-year-old Tamara Drayton was found floating face-down in the pool of her family's idyllic mansion in the south of France, leaving her twin brother, golden-boy Blake, to pick up the pieces of their shattered family. Also left behind was their sister Nina who, at six years old, became the youngest person ever to testify in a French murder trial. Because she's the only one who saw what happened--who watched as her babysitter, Josie Jackson, pushed Tamara under the water, and held her there until she stopped breathing. Didn't she? Twenty years later, Nina's memories have faded, leaving her with no idea of what really transpired that night. When a new true crime documentary about her sister's murder is announced, Nina thinks this might be her chance to finally find out"--